DETERMINAN STRUKTUR MODAL PERUSAHAAN INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI - Febriani, Arini Dwi; Kristanti, Farida Titik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The tight competition in the era of globalization requires companies to be able to maximize its value in order to remain competitive with other companies. Decision in the formation of capital structure is one of the important decisions that can maximize the value of the company. When the process of forming an optimal capital structure, it is important for financial managers to pay attention to the determinants of the capital structure. This study aims to investigate the factors that determine the capital structure in the infrastructure, utilities, and transportation companies. Several factors investigated for its effect on capital structure are profitability, company growth, company size, assets structure, non-debt tax shield, and business risk. Purposive sampling is a method used in research sampling, in which  216   research samples were obtained consisting of 36 companies with a  6 years study period, namely  2013-2018. The panel data regression model is used as a model to investigate the determinants of capital structure. The results show that the company growth and the company size negatively affected the capital structure, while profitability, asset structure, non-debt tax shield, and business risk did not affect the capital structure.